The Effect of TPS-Type Cooperative Learning Model on Student Learning Motivation at STIMI Meulaboh - Nur Fajri; Eka Syani; Yenni Muflihan (LPPM Politeknik Aceh Selatan, 2021)
Successful learning is learning that can make students motivated, fun and comfortable in the teaching and learning process. Cooperative learning is one way for lecturers so that students can enjoy learning. Therefore, it is very important for lecturers to create fun and comfortable student learning without pressure. The purpose of this study was to determine the effect of the application of the TPS type cooperative learning model on students' learning motivation at STIMI Meulaboh. This type of research is experimental research by applying the TPS type cooperative learning model and the results are by distributing questionnaires and observations. The results of this study are the TPS type cooperative learning model has an effect on students' learning motivation. Therefore, it can be said that the TPS type of cooperative learning model is feasible to be used in the Economics I statistics learning process in the classroom to improve students' understanding and quality of learning.